SKRINING FITOKIMIA DAN PENETAPAN KADAR FLAVONOID TOTAL TERHADAP EKSTRAK ETANOL SAWI PAHIT (Brassica juncea (L.) Czern) DENGAN METODE SPEKTROFOTOMETRI UV-VIS - Mambang, D. Elsya Putri; Nasution, Haris Munandar; Friyani, Lilah (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
Mustard is a vegetable commodity that has good commercial value and prospects. Apart from being viewed from the climatological, technical and social economic point of view, it is also very supportive, so that it has the feasibility to be cultivated in Indonesia and this vegetable is a type of vegetable that is favored by all groups of people. Mustard is a vegetable that has many benefits for the body.The stages of this research include sample collection and plant processing, plant identification, manufacture of ethanol extract of bitter mustard leaf, determination of water content, phytochemical screening and determination of total flavonoid content by UV-Visible spectrophotometry.This study aims to determine the total flavonoid content of bitter mustard greens and to determine the characteristics, class of chemical compounds, and total flavonoid value of bitter mustard (Brassica juncea (L.) Czern) extract by UV-VIS spectrophotometry.